Icelandic eiders—a few observations - Palmer, Ralph S (Wildfowl, 1973)
These notes are based on a visit, 25-29 May inclusive, in 1972, to the eider farm of Gisli Vagnsson, at Myrar, on the north side of Dyrafjord in northwest Iceland.